READING HABITS AND THE STUDENTS’ WRITING SKILL AMONG EFL LEARNERS - Setyaningrum, Riya Risqi; Fatmawati, Riryn; Nahdiah, Sirli (TELL - US JOURNAL, 2022)
The study aims to find out the reading habits of EFL students to find out the writing skill of students and to find out a significant relationship between students' reading habits and the writing skill of students in the informatics engineering study program UNISLA. The method of study is quantitative with a correlation descriptive design. The data collection is documentation of students’ score in portfolio writing and the questionnaire’s score of reading habits.  The instruments of research are the report mark of students’ writing ability and the questionnaire.  The finding showed that the value of “r” is 0.41. It means that the correlation between students' reading habits and writing skill between English learners of Informatics Engineering at UNISLA in the academic year 2021/2022 were "Fairly High Correlation". A grade of r (0.41) ≥ of r-table (0.317) proves that Ha is accepted, so there is a significant relationship between students' reading habits and writing skill between Informatics Engineering study program learners at UNISLA in the academic year 2021/2022. Finally, researchers suggested to English teachers should get students interested in reading books by providing facilities and motivation to students. If the student has a high reading habit, the student will write easily in English.